Crisis vitales y depresión en un paciente con insuficiencia renal crónica - Roelas Fajardo, Gabriela Carolina (2019)
This research Works stems from the realization of pre-professional practices in the “Dial Ríos” Vinces Hemodialysis Unit aimed at providing treatments to people with Renal Failure, with the aim of centralizing a specific case study one was taken into account of the problems in said entity. Chronic renal failure is a catastrophic disease that affects the functionality of the kidneys. People diagnosed with this disease, experience a series of sudden emotional changes in their lives due to the disease itself and treatment, in some cases suffering from psychological disorders such as depression, as a result of the lack of adaptation to it. Vital crises that occur throughout the patient's life. Gathering all the required information, it was possible to reach a diagnostic approach that is described in the next pages of this paper, psychotherapeutic techniques were also implemented that gave structure to a psychotherapeutic scheme of cognitive-behavioral approach as a proposal for the solution of said case study